Transanal Endoscopic Operation under spinal anaesthesia. Issue 7 (25th February 2016) - Arezzo, A.; Cortese, G.; Arolfo, S.; Bullano, A.; Passera, R.; Galietti, E.; Morino, M.
Abstract : Background: Transanal Endoscopic Operation (TEO ® ) for rectal benign lesions and early rectal cancer may provide better oncological outcomes than flexible endoscopy. The major advantage of flexible endoscopy is that it does not require general anaesthesia. This prospective observational study assessed the feasibility and safety of TEO ® performed under spinal anaesthesia. Methods: The study population comprised eligible consecutive patients who underwent TEO ® under spinal anaesthesia with curative or palliative intent for rectal neoplasms larger than 20 mm in diameter or for recurrent lesions of any size. The primary endpoints were feasibility and safety; secondary endpoints were postoperative pain, as measured on a visual analogue scale, heart rate, systolic and diastolic BP, opioid requested, postoperative nausea or vomiting, and urinary retention. Results: The study included 50 patients (median age 70 years; 29 men and 21 women). No intraoperative complications occurred. The median duration of operation was 60 (range 20–165) min. No opioids were requested during the perioperative or postoperative period. The median postoperative pain score was 0 at 4, 8, 24 and 48 h after surgery. There were no significant fluctuations in heart rate, systolic and diastolic BP up to 48 h after the procedure ( P =  0·379, P =  0·386 and P =  0·617 respectively). Postoperative nausea and vomiting occurred in one patient, and urinary retention in four. Conclusion: TEO ® under spinal anaesthesia was safe and feasible with no conversions to general anaesthesia. Abstract : Safe